2021
DOI: 10.3390/cells10123544
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Self-DNA—A Potential Source of Chronic Inflammation in Aging

Abstract: Aging is the consequence of a lifelong accumulation of stochastic damage to tissues and cellular components. Advancing age closely associates with elevated markers of innate immunity and low-grade chronic inflammation, probably reflecting steady increasing incidents of cellular and tissue damage over the life course. The DNA sensing cGAS-STING signaling pathway is activated by misplaced cytosolic self-DNA, which then initiates the innate immune responses. Here, we hypothesize that the stochastic release of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 227 publications
(279 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that unrepaired DNA damage will accelerate the rate of aging [ 39 ]. mtDNA begins to damage over time, and the ability of cells to produce energy is gradually lost, leading to aging [ 40 ]. Mitochondria, known as the power plant of cells, produce 90% of chemical energy to maintain cell survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that unrepaired DNA damage will accelerate the rate of aging [ 39 ]. mtDNA begins to damage over time, and the ability of cells to produce energy is gradually lost, leading to aging [ 40 ]. Mitochondria, known as the power plant of cells, produce 90% of chemical energy to maintain cell survival [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advancing age has been reported to be linked to a condition of chronic low-grade inflammation in various tissues ( 9 ), which is known as “inflammaging” and characterized by elevated levels of circulating pro-inflammatory mediators ( 10 ), including the cytokines interleukin 1β (IL-1β), tumor necrosis factor-α (TNF-α), and IL-6 ( 11 , 12 ). As an important transcription factor for apoptosis, immunity, and inflammation ( 13 ), nuclear factor-kappa B (NF-κB), as a decisive molecule in muscle atrophy ( 14 ), has been illustrated to be activated in multiple organs of the elderly and aging animals, including aged muscles ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The order of events leading to mitochondrial dysfunction in APTX deficient cells are currently unclear. However, it is known that loss of function of APTX leads to decreased ATP synthesis, increased DNA damage (particularly in mitochondria), increased ROS production and alterations in mitochondrial morphology, all are functions which have profound effect on normal cell function, including the release of self-DNA into the cytosol (Akbari et al, 2021). The presence of self-and foreign DNA in the cytosol can lead to immune responses and inflammation, which are activated by DNA sensing pathways including cGAS-STING signaling (Gregg et al, 2019;Akbari et al, 2021).…”
Section: Introductionmentioning
confidence: 99%